Prognostic value of serum parathyroid hormone in ST-elevation myocardial infarction patients - Obradović Slobodan; Vukotić Snježana; Banović Marko; Džudović Boris; Marinković Jelena; Vujanić Svetlana; Obradović Dragana (Vojnosanitetski Pregled)
Background/Aim. Parathyroid hormone (PTH) is an important messenger in the regeneration process which might influence the outcome of patients with ST-segment elevation myocardial infarction (STEMI). The aim of this study was to investigate the role of PTH in comparison to other traditionally used markers for the prediction of heart failure in STEMI patients. Methods. In 165 consecutive patients with STEMI treated with primary percutaneous coronary intervention (PCI), blood concentrations of PTH, C-reactive protein (CRP), B-type natriuretic peptide (BNP), creatine kinase MB (CK-MB) and admission glycaemia (AG) were measured during the first three days after admission and correlated to the primary outcome - episodes of acute heart failure in the period of six months. Results. The area under the ROC curve of the maximal serum concentration of PTH was the largest among the measured biomarkers (0.867 vs 0.835 vs 0.832 vs 0.627 vs 0.619, for PTH, CRP, BNP, CK-MB and AG, respectively) for the prediction of primary outcome. The maximal PTH level adjusted to several risk factors had an independent prediction value for primary outcome (p < 0.001). In addition, PTH improved the prediction of primary outcome when added to the other markers in the model [cstatistic with BNP, CRP, CK-MB and AG was 0.908 (95% CI 0.849-0.967)], and when PTH was added, it was 0.931 (0.883-0.980), with p < 0.001 for the discrimination. Conclusion. Serum concentration of PTH early in the course of STEMI can predict acute heart failure episodes in the first six months in patients treated with primary PCI.